Alliance Concentration in Multinational Companies - Bos, Brenda; Faems, Dries; Noseleit, Florian (Strategic Management Journal, 2017)
[Research summary: This article explores the distribution of alliances across firms’ internal structure. Focusing on multinational companies, we examine the impact of alliance portfolio concentration—i.e., the extent to which alliances are concentrated within a limited number of geographic units—on focal firms’ performance. Relying on Knowledge-Based View (KBV) insights, we hypothesize that an increase in alliance portfolio concentration positively influences firm performance and that alliance portfolio size negatively moderates this relationship. Our empirical results enrich the emerging capability perspective on alliance portfolios, point to the relevance of conceptualizing focal firms in alliance portfolio research as polylithic entities instead of monolithic ones, and provide new insights into how firms create value by potentially recombining externally accessed knowledge. Managerial summary:In the setting of multinational companies, we examine whether alliance activities are concentrated in a limited number of subsidiaries or are highly dispersed across multiple subsidiaries. We find that, over time, firms exhibit different patterns in terms of alliance portfolio concentration. In addition, the results show that, for MNCs with a relatively small alliance portfolio, an increase in alliance portfolio concentration is positively related to their financial performance. However, when MNCs’ alliance portfolios are relatively large, the relationship between alliance portfolio concentration and firm performance becomes negative. Jointly, these findings suggest that the distribution of alliances across firms’ internal structure is an important factor in shaping potential knowledge recombination benefits from alliance portfolios.]